Sefer ha-Pardes by Jedaiah ha-Penini A Critical Edition with English Translation - Torollo, David (Semitic Languages and Cultures, 2022)
This groundbreaking new work is the first full critical edition and English translation of the Hebrew book Sefer ha-Pardes [The Book of the Orchard], written at the end of the thirteenth century by the Provençal Jewish author Jedaiah ha-Penini. It is purportedly an example of musar: a compilation of wise epigrams and meshalim [parables] that teach moral lessons on different topics, such as the service of God, friendship, the deceitfulness of the world, medicine, logic, music, magic, and poetry. However, it is in reality a compendium of sayings that reveal the author's personal views and feelings on a variety of religious topics, secular sciences, and their practitioners. David Torollo presents a fluent and illuminating English-Hebrew parallel text based on four sixteenth-century witnesses: three manuscripts and a printed edition. A rigorous study accompanies and contextualises the Hebrew work, exploring Sefer ha-Pardes's transmission and reception in different places over time; its structure and content; its place in the intellectual environment and literary tradition of Provence; and possible lines of enquiry for future research. This essential new work offers a significant contribution to scholarship in the field of Medieval Hebrew Hispano-Provencal literature.